Microleakage and nanoleakage: Influence of laser in cavity preparation and dentin pretreatment - Araujo, R. M.; Eduardo, C. D.; Junior, SLLD; Araujo, MAM; Loffredo, L. D. (Mary Ann Liebert, Inc., 2001)
Objective: the purpose of this study was to verify if the application of the Nd:YAG laser following pretreatment of dentin with adhesive systems that were not light cured in class V cavities and were prepared with Er:YAG laser would promote better sealing of the gingival margins when compared to cavities prepared the conventional way. Background Data: Previous studies had shown that the pretreatment of dentin with laser irradiation after the application of an adhesive system is efficient in achieving higher shear bond and tensile bond strength. Materials and Methods: Er:YAG laser (Kavo-Key, Germany) with 350 mJ, 4 Hz, and 116.7 J/cm(2) was used for cavity preparation. The conventional preparation was made with diamond bur mounted in high-speed turbine. Dentin treatment was accomplished using an Nd:YAG laser (Pulse Master 1000, ADT. USA) at 60 mJ, 10 Hz, and 74.65/cm(2) following application of the adhesive system. The cavities were stored with Single Bond/Z100 and Prime & Bond NT/TPH. Eighty bovine incisors were used, and class V preparations were done at buccal and lingual surfaces divided into eight groups: (1) Er:YAG preparation + Prime & Bond NT + TPH; (2) Er:YAG preparation + Single Bond + Z100; (3) Er:YAG preparation + Single Bond + Nd:YAG + Z100; (4) Er:YAG preparation + Prime & Bond NT + Nd:YAG + TPH; (5) conventional preparation + Prime & Bond NT + TPH; (6) conventional preparation + Single Bond + Z100; (7) conventional preparation + Single Bond + Nd:YAG + Z100; (8) conventional preparation + Prime & Bond NT + Nd:YAG + TPH. All specimens were thermocycled for 300 full cycles between 5 degreesC +/- 2 degreesC and 55 degreesC +/- 2 degreesC (dwell time of 30 sec), and stored in 50% silver nitrate solution for 24 h soaked in photodeveloping solution and exposed to fluorescent light for 6 h. After this procedure, the specimens were sectioned longitudinally in 3 portions and the extension of microleakage at the gingival wall was determined following a criteria ranging from 0 to 4 using scanning electron microscopy (SEM). The medium portion sectioned of each specimen was polished and prepared for nanoleakage avaliation by SEM. Results: Kruskall-Wallis and Miller statistical tests determined that group 3 presented less microleakage and nanoleakage. Conclusion: Application of the Nd:YAG laser following pretreatment of dentin with adhesive Single Bond non-photocured Single Bond adhesive in cavities prepared with Er:YAG promote better sealing of the gingival margins.